Investigation of Workers' Food and Suggestions as to Dietary - Hill, Leonard, Sir, 1866- (London : His Majesty's Stationery Office)
1917-10 1917 1910s 12 pages 5 Boys and girls over 10 years require as much as men and women, for they are not only very active, but are growing. RESULTS OF INQUIRY. 8. Canteen Meals.— In order to determine the kinds of dietaries provided for munition workers, specimen meals were obtained, by personal visit or otherwise, from a number of canteens attached to munition works, and to serve as a contrast, from other sources as well. The amount of protein, fat, and carbohydrate in each meal were estimated and the calorie value was calculated. See Table 1.* TABLE 1. Factory or Restaurant. Style of Catering. Ingredients. Dry Weight in Grammes. Total Calories. Protein. Fat. Carbohydrate. Ash. Total. No. 4 Professional Potatoes, cabbage, steak pudding, jam roll 35 42 127 5 209 1,053 No. 5 Amateur Roast mutton, boiled potatoes, cabbage and rice pudding 48 51 87 7 193 1,025 No. 6 Amateur Potatoes, cabbage, steak pudding, rice pudding 36 30 93 4 163 806 A students' club Professional Roast beef, boiled potatoes, cabbage, syrup roll 34 28 101 3 166 814 Popular restaurant Professional Steak pudding, potatoes and cabbage, syrup pudding 44 42 193 3 282 1,362 No. 7 Amateur Steak pudding, peas and potatoes, jam roll, rice pudding 51 42 204 8 305 1,433 Working class restaurant Professional Meat pudding, potatoes, cabbage, suet pudding 29 39 128 4 200 1,004 No. 3 (A) Works Roast beef, potatoes and peas, sago pudding 31 31 131 5 198 948 No. 3 (B) Works Liver and bacon, potatoes and peas, currant pudding 55 30 160 6 251 1,155 No. 1 Professional Meat pudding, cabbage, potatoes and jam roll 32 52.1 178.4 7.5 270 1,346 No. 2 (A) Works Roast mutton, potatoes, peas, currant pudding, bread 55.5 22.8 180.1 7.1 258.4 1,177.9 No.2 (B) Works Liver and bacon, potatoes and peas, currant pudding, bread 58.7 30.1 180.2 7.3 268.9 1,259 *The method of making the estimations was the same in each ease. The ingredients were all thoroughly mixed after weighing each separately so that dietaries could afterwards be constructed from the weights. An aliquot part of the intimate mixture was thoroughly dried and weighed. In the dry material protein was determined from a nitrogen estimation, the fat by other extractions in a Soxhlets apparatus, the ash by burning and weighing, and the carbohydrate by difference. In this way the amounts of dry protein, fat, and carbohydrate respectively in the meal were obtained, and from these the calorie value was calculated. (B 10570) A 3 127/NU/5/5/1/1